Equine Influenza: Epidemiology, Pathogenesis, and Strategies for Prevention and Control - Francesco Branda; Dong Keon Yon; Mattia Albanese; Erica Binetti; Marta Giovanetti; Alessandra Ciccozzi; Massimo Ciccozzi; Fabio Scarpa; Giancarlo Ceccarelli (Viruses)
Equine influenza (EI) is a highly contagious respiratory disease caused by the equine influenza virus (EIV), posing a significant threat to equine populations worldwide. EIV exhibits considerable antigenic variability due to its segmented genome, complicating long-term disease control efforts. Although infections are rarely fatal, EIV’s high transmissibility results in widespread outbreaks, leading to substantial morbidity and considerable economic impacts on veterinary care, quarantine, and equestrian activities. The H3N8 subtype has undergone significant antigenic evolution, resulting in the emergence of distinct lineages, including Eurasian and American, with the Florida sublineage being particularly prevalent. Continuous genetic surveillance and regular updates to vaccine formulations are necessary to address antigenic drift and maintain vaccination efficacy. Additionally, rare cross-species transmissions have raised concerns regarding the zoonotic potential of EIV. This review provides a comprehensive overview of the epidemiology, pathogenesis, and prevention of EI, emphasizing vaccination strategies and addressing the socio-economic consequences of the disease in regions where the equine industry is vital.